Clinical utility of TERT promoter mutations and ALK rearrangement in thyroid cancer patients with a high prevalence of the BRAF V600E mutation - Bae, Ja Seong (Diagn Pathol, 2016)
BACKGROUND: Mutations in the TERT promoter, ALK rearrangement, and the BRAF V600E mutation are associated with aggressive clinicopathologic features in thyroid cancers. However, little is known about the impact of TERT promoter mutations and ALK rearrangement in thyroid cancer patients with a high prevalence of BRAF mutations. METHODS: We performed Sanger sequencing to detect BRAF V600E and TERT promoter mutations and both immunohistochemistry and fluorescence in situ hybridization to identify ALK rearrangement on 243 thyroid cancers. RESULTS: TERT promoter mutations were not present in 192 well-differentiated thyroid carcinomas (WDTC) without distant metastasis or in 9 medullary carcinomas. However, the mutations did occur in 40 % (12/30) of WDTC with distant metastasis, 29 % (2/7) of poorly differentiated carcinomas and 60 % (3/5) of anaplastic carcinomas. ALK rearrangement was not present in all thyroid cancers. The BRAF V600E mutation was more frequently found in WDTC without distant metastasis than in WDTC with distant metastasis (p = 0.007). In the cohort of WDTC with distant metastasis, patients with wild-type BRAF and TERT promoter had a significantly higher response rate after radioiodine therapy (p = 0.024), whereas the BRAF V600E mutation was significantly correlated with progressive disease (p = 0.025). CONCLUSIONS: The TERT promoter mutation is an independent predictor for distant metastasis of WDTC, but ALK testing is not useful for clinical decision-making in Korean patients with a high prevalence of the BRAF V600E mutation. Radioiodine therapy for distant metastasis of WDTC is most effective in patients without BRAF V600E and TERT promoter mutations.